Exchange of Nonmonetary Assets: An Interpretation Problem. - Smith, Ralph E.; Haried, Andrew A. (The Accounting Review, 1977)
ABSTRACT: Accounting Principles Board Opinion No. 29 provides that an exchange of nonmonetary assets normally should be accounted for as if the exchange involved monetary assets. One exception to this provision is the case in which a productive asset not held for resale is exchanged for a similar productive asset in which case the asset received is recorded at the book value of the asset relinquished. However, an interpretive problem arises if a significant amount of cash is included in such an exchange. This paper describes the problem and suggests a solution.